Evaluating Industrial Areas with Spatial Multicriteria Analysis (SMCA) - Noer, Marwah; Wibowo, Adi (MO.RI Publishing, 2024)
The assessment of industrial areas stands as a pivotal challenge, increasingly recognized for its urgency across various regions. The industrial sector is a cornerstone of national economic development, contributing significantly to growth and enhancing community welfare. Nonetheless, the establishment of industries also poses environmental and societal risks, primarily due to potential pollution. This study focuses on evaluating the suitability of industrial zones in East Cikarang District, Bekasi Regency, through spatial analysis, benchmarking findings against government-regulated industrial areas as outlined in the Bekasi Regency spatial plan for 2011-2031. Employing Spatial Multicriteria Analysis (SMCA) via ILWIS software, this research aims to deliver a comprehensive assessment of industrial locations by considering variables such as proximity to roads, rivers, settlements, land slope, and alignment with designated industrial zones in the regional spatial plan. The analysis reveals a nuanced classification of industrial suitability, with 48.55% of the area deemed highly suitable, indicating a substantial portion of East Cikarang District is favorable for industrial development. Conversely, a smaller segment falls into the less suitable or unsuitable categories. Overall, the study concludes that 55% of the region qualifies as suitable for industrial purposes based on the SMCA-derived spatial model, with 98.1% of the assessed area aligning with the criteria for designated industrial zones. These insights are intended to guide industrial planning and environmental management strategies, fostering sustainable development within the region.